Renewed Geoarchaeological Investigations of Mwanganda's Village (Elephant Butchery Site), Karonga, Malawi. Issue 2 (5th February 2014) - Wright, David K.; Thompson, Jessica; Mackay, Alex; Welling, Menno; Forman, Steven L.; Price, Gilbert; Zhao, Jian‐xin; Cohen, Andrew S.; Malijani, Oris; Gomani‐Chindebvu, Elizabeth
<x xml:space="preserve">Abstract</x> The site of Mwanganda's Village, located along a paleochannel in northern Malawi, is one of only a few sites that have characterized the Middle Stone Age (MSA) of Malawi for decades (Clark & Haynes, 1970; Clark et al., 1970; Kaufulu, 1990). The Malawi Earlier‐Middle Stone Age Project has re‐examined the site using new mapping and chronometric tools in order to reinterpret the site's significance within the context of current debates surrounding human origins and the potential role the environment played in shaping human behavior. The new data do not support the previous hypothesis that the site was an elephant butchery location (contra Clark & Haynes, 1970; Clark et al., 1970; Kaufulu, 1990). Instead, the evidence shows successive colonization of riparian corridors by MSA hunter‐gatherers focused on exploiting localized resources during periods of generally humid climates while other lakes desiccated across Africa. We challenge the hypothesis that stable and intermediately high lake levels within the African Rift Valley System (sensu Trauth et al., 2010) catalyzed the evolution of regional interaction networks between 42 and 22 ka. Instead, we interpret the evidence to suggest that regional variants of technology persist into the late MSA as foragers focused on exploiting resources from local catchments.